AID in Antibody Diversification: There and Back Again. Issue 7 (July 2020) - Feng, Yuqing; Seija, Noé; Di Noia, Javier M.; Martin, Alberto
Abstract : Activation-Induced cytidine Deaminase (AID) initiates affinity maturation and isotype switching by deaminating deoxycytidines within immunoglobulin genes, leading to somatic hypermutation (SHM) and class switch recombination (CSR). AID thus potentiates the humoral response to clear pathogens. Marking the 20th anniversary of the discovery of AID, we review the current understanding of AID function. We discuss AID biochemistry and how error-free forms of DNA repair are co-opted to prioritize mutagenesis over accuracy during antibody diversification. We discuss the regulation of DNA double-strand break (DSB) repair pathways during CSR. We describe genomic targeting of AID as a multilayered process involving chromatin architecture, cis - and trans -acting factors, and determining mutagenesis – distinct from AID occupancy at loci that are spared from mutation. Highlights: Subverted base excision repair (BER) and mismatch repair (MMR) pathways act concertedly to generate antibody sequence diversity during SHM. In CSR, DNA DSBs are repaired by the nonhomologous end-joining pathway involving the 53BP1–Rif1–Shieldin axis, and by an alternative end-joining pathway involving HMCES (5-Hydroxymethylcytosine binding, ES-cell-specific) that binds and protects resected DSB ends. Genomic targeting of AID appears to be multilayered, with inbuilt redundancy, but robust enough to ensure that most of the genome is spared from AID activity. Cis elements and genome topology act together with trans-acting factors involved in transcription and RNA processing to determine AID activity at specific Ig regions. Other loci sharing genomic and transcriptional features with the Ig are collaterally targeted during SHM and CSR.